Reaction against liver cells by human antiactin antibodies purified by affinity chromatography. Issue 7 (July 1982) - Riison, K; Diederichsen, H; Andersen, I
Abstract : Human antiactin antibodies were isolated from human smooth muscle antibodies by affinity chromatography using actin extracted from rabbit striated muscle and coupled to activated CH-Sepharose 4B. The eluate contained IgG and IgM smooth muscle antibodies reacting against muscularis mucosae of the stomach and blood vessels. Further the eluate contained IgM antibodies acting against the surface of isolated hepatocytes and the periphery of hepatocytes of sections of liver cells. These results indicate that antiactin antibodies possibly react with the hepatocyte membrane as has been described with regard to other antibodies.